Study of Biopharmaceutical Properties of Recommended Capsules "Prostad" by in Vitro and in Vivo Method - Kh. M. Yunusova; Sh. Kh. Sunnatov (Scientific Trends, 2025)
It has been established that the dissolution test characterizes the biological availability of the drug as a first approximation, since in practice there is a very frequent correlation between the rate of dissolution and absorption. The study of the biological availability of drugs, preparations or their dosage forms usually begins with in vitro experiments and ends with in vivo experiments with further research in clinical conditions. The next series of experiments were devoted to studying the rate of release of active substances by the in vitro method from the recommended capsules "Prostad", obtained on the basis of the dry extract "Prostad". At present, there are standardized pharmacopoeial requirements for conducting the "Dissolution" test, which cover devices, dissolution media, temperature conditions, testing duration and statistical methods for processing the obtained results. In this experiment, the generally accepted "Rotating basket" method included in the State Pharmacopoeia of the Republic of Uzbekistan was used. This report presents the results of studying the pharmacological properties of the dry extract based on the narrow-leaved fireweed "Prostad" recommended for prostatitis by the in vitro and in vivo methods.
Keywords: Pharmacotechnological aspects, effective excipients, packaging materials, in vitro, in vivo, methods.